Living in digital worlds designing the digital public space - Jacobs, Naomi 1981-; Cooper, Rachel 1953- (Routledge, 2018)
"Living in Digital Worlds investigates the relationship between human society and technology, as our private and particularly our public lives are increasingly undertaken in spaces that are inherently digital: digital public spaces. The book unpicks why digital technology is such an inextricable part of modern society, first by examining the historical relationship between technological development and the early progression of human sociality. This is then followed by an examination of the ways in which modern life is currently being impacted by the expansion of digital information and devices into multiple aspects of our lives, including focuses on privacy, bias and ownership in digital spaces. Finally, it explores potential future developments and their implications, and proposes that it is crucial to consider the design of technology and systems in order to support a positive and beneficial direction of change. Each chapter includes case studies, primarily drawn from The Creative Exchange, a fiveyear programme which ran from 2012 to 2016 to explore the notion of the digital public space through collaborative cross-sector research."--Provided by publisher